Revisión a la interpretación del principio de la buena fe para su aplicación por parte de los servidores públicos (2019)
The need to address a comparative judgment between the specific purpose that guides the rule in the legal system and the purpose that seeks the Administrator to exercise the powers conferred upon it, through the application of the Principle of good faith, constitutionalized, allowed to determine that beyond the constitutionalization of this principle of law so that it becomes a binding element of the actions of the parties in the relations that arise between the State and its administrated ended up turning it into the trench of corruption, given that the system of norms in Colombia, today does not have the sanction to punish its distortion, its omission and its inapplication or application without due rigor within the “must be”. So that the lack of coherence, interdependence and reciprocity between the application of this principle and that of legality creates a “legal limbo” in which beyond making it a binding element, it becomes an escape door for both public servants as administrators seek their protection before verifying and applying the principle of legality in their actions.